Advancing The food system for growth, Job creation and better Nutrition - Fouad, Gihan (2019)
as part of the IFPRI-Egypt Seminar Series- funded by the United States Agency for International Development (USAID) project called “Evaluating Impact and Building Capacity” (EIBC) that is implemented by IFPRI.